(untitled) (Global Journal of Human-Social Science, 2013)
This study aimed at examining the prevalence of under financing in Local Government Authorities of Tanzania, taking Bahi District Council as a case study. Specifically, the study intended to examine the causes, extent of under financing and effects associated with under financing in LGAs. The study adopted cross sectional design. The case study was also used to get an in-depth data on under financing. Questionnaires were used during survey of 115 heads of households. The documentary review and Focus group discussion were used to collect secondary data and primary data related to under financing respectively. The analysis of data was done using SPSS. The findings of this study revealed that, first, under financing in LGA was triggered by fraud, delay in reporting and heavily depending on donors; second, under financing resulted into a number of negative effects such as inability to provide optimal social and economic services. The study concludes that LGAs are not free from under financing. This study therefore recommends that the council and other actors should diversify sources of revenue to be able to absorb the shocks of under financing and reduce donor dependency